Efficacy and tolerability of Amitriptyline versus Fluoxetine in the treatment of patients with somatoform disorder: A randomized comparative trial - Joshi, S.; Pandey, AK; Sapkota, N. (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Somatoform disorder(SFD) is a heterogeneous group of disorders with difficult diagnostic problems and skepticisms regarding the treatability. Though a common diagnosis among psychiatrists and physicians alike, there are limited studies on its treatment, more so in developing countries. Emerging evidences suggest that antidepressants may potentially be effective and reduce disability, costs, and patient dissatisfaction. Objective: This study aims to compare the effectiveness of Amitriptyline and Fluoxetine in the treatment of patients with SFD presenting to department of Psychiatry at BPKIHS, Dharan. Method: It is a hospital based open label, randomized comparative study which included 60 patients meeting ICD DCR criteria for SFD. The patients were assigned to Fluoxetine (30 patients) and Amitriptyline (30 patients) treatment groups as per block randomization and followed up for 8 weeks. The clinical effects were tested at baseline and subsequent evaluations with Patient Health Questionnaire-15(PHQ 15) and side effects enquired. Socio-demographic variables and other medical information were collected in a structured proforma. Result: The reduction in PHQ 15 score was statistically significant in both the treatment groups. The reduction in PHQ 15 score was statistically faster in Fluoxetine group than Amitriptyline group from week 2 to week 4. Amitriptyline was more frequently associated with side effects than Fluoxetine. Conclusion: Both Amitriptyline and Fluoxetine were comparable in effectiveness in SFD with Fluoxetine more tolerated than Amitriptyline.